Mecanismos de ação antinociceptiva do extrato etanólico da entrecasca da Caesalpinia pyramidalis - Santos, Cliomar Alves dos (2015)
Pain is one of the major health problems, leading people to search for treatment. A pharmacological screening showed that the Caesalpinia pyramidalis ethanol extract (EE) reduces nociception behavior in the writhing, formalin, and hot plate tests in mice. In order to assess the mechanism of action of EE of C. pyramidalis, substrate, antagonists or inhibitors of different pathways involved in nociception were used in the writhing model. To select the dose, mice (n = 6 per group) were pretreated with EE of C. pyramidalis (10, 30, or 100 mg/kg, p.o.) vehicle (Tween 80, 0.2% in saline, 10 mL/kg, p.o.) or acetylsalicylic acid (ASA, 300 mg/kg, p.o.) 1 hour before the administration of acetic acid (0.6%, 0.1 ml/10 g, i.p.). Subsequently, different groups of animals were pretreated, intraperitoneally, with L-arginine (NO precursor, 600 mg/kg, 15 min), methilene blue (NO/cGMP, way inhibitor, 20 mg/kg, 15 min), glibenclamide (K+-ATP channels inhibitor, 3 mg/kg, 15 min), atropine (muscarinic-cholinergic receptors antagonist, 0.1 mg/kg, 15 min), prazosina (α1-adrenoceptor antagonist, 0.15 mg/kg, 15 min), yohimbine (α2-adrenoceptor antagonist, 0.15 mg/kg, 15 min), haloperidol (dopaminergic receptors antagonist, 2 mg/kg, 15 min), caffeine (adenosinergic receptors antagonist, 3 mg/kg, 15 min), flumazenil (gabaergic receptors antagonist, 3 mg/kg, 15 min) or, reserpine (inhibitor of monoamine receiving, 5 mg/kg, 24 h), and were treated with EE of C. pyramidalis (30 mg/kg, p.o.), vehicle (p.o.), L-NOARG (NOS inhibitor, 75 mg/kg, i.p.), acetylcholine (muscarinic receptor agonist, 1 mg/kg, i.p.), phenylephrine (α1-adrenoceptor agonist, 1 mg/kg, i.p.), clonidine (α2-adrenoceptor agonist, 0,1 mg/kg, i.p.), adenosine (adenosinergic receptors agonist, 100 mg/kg, i.p.), diazepam (gabaergic receptors agonist, 1,5 mg/kg, i.p.) or, clomipramine (neuronal receiving monoamines inhibitor, 10 mg/kg, i.p.). Sixty min after the different treatments writhing was conducted. Besides, another animal groups, 60 min before the administration of vehicle, doses of 10, 30, or 100 mg/kg of the EE of C. pyramidalis and 30 min before administration of the received morphine (3 mg/kg, i.p.) in order to be subjected to testing of capsaicin (20 μL, 1.6 mg/paw) or glutamate (20 μL, 20 μmol/paw). All experimental controls functioned as expected pharmacological action, observing their reversals of the analgesic effect, when comparing with animals that received different treatments with the drugs used. The number of writes was lower when received the EE from C. pyramidalis in the doses of 30 and 100 mg/kg (P < 0.001), in a dose-dependent manner, when was compared with the animals that received vehicle, choosing the dose of 30 mg/kg (p.o.) to this study. There was a reversal of the antinociceptive effect of the EE C. pyramidalis action when the animals were pretreated with L-arginine (P < 0.001), methylene blue (P < 0.05), glibenclamide (P < 0.001), atropine (P < 0.001), yohimbine (P < 0.05), and flumazenil (P < 0.001) and the reversion was not observed when administered prazosin, haloperidol, reserpine, and caffeine. The results showed, that the animals reduced the licking/biting time at the dose of 100 mg/kg in the capsaicin test (P < 0.05) and in all doses in the glutamate test (P <0.01). Concludes that the EE of C. pyramidalis presents its antinociceptive effect, acting synergistically in pathways of L-arginine/NO, NO/cGMP, K+ channel-ATP sensitive, muscarinic cholinergic, α2-adrenergic and GABAergic, and involve the participation of glutamate and capsaicin in the antinociceptive effect.